Bibliometric Analysis of the Trend of Virtual Reality Use in Physics Learning: Focusing on the Kuula Platform and Its Impact on the Learning Outcomes of Fluid Material - Rince Aida Rostika; Bodi Gunawan (Journal of Sustainable Educational Technology and Innovation, 2025)
Background of Study: Fluid material in physics is often difficult to understand due to its abstract nature and the need for dynamic visualization. VR technology is considered capable of providing an immersive and interactive learning experience, thereby supporting student understanding and engagement more effectively.Aims and Scope of Paper: This research aims to analyze the potential development of VR(Virtual Reality) based learning media in physics education, focusing on the use of the Kuula platform to improve student learning outcomes on fluid material in 11th-grade high school.Methods: In this study, a bibliometric analysis was conducted to explore publication trends and scientific findings related to the application of VR in physics learning, especially those relevant to the Kuula platform and fluid topics. Data were obtained from 145 Scopus-indexed articles from 2020 to 2025 and analyzed using software Biblioshiny and VOSviewer.Result: The analysis shows an increase in publications related to VR in education, with a primary focus on enhancing student engagement, learning motivation, and understanding of abstract concepts. Bibliometric visualization indicates a strong connection between VR and the fields of education, technology, and health, with China and the United States emerging as dominant contributors. However, the decline in average citations per article suggests the need to improve the quality and depth of research in this area.Conclusion: Overall, these findings affirm that VR-based physics learning media have significant potential in improving student learning outcomes on fluid topics, as well as highlighting the importance of developing a curriculum responsive to advancements in educational technology.